PFT1, a transcriptional Mediator complex subunit, controls root hair differentiation through reactive oxygen species (ROS) distribution in Arabidopsis - Sundaravelpandian, Kalaipandian (The New phytologist, 2013)
© 2012 The Authors. New Phytologist © 2012 New Phytologist Trust.